Mao Zedong, Sinization of Marxism, and Traditional Chinese Thought Culture - Chenshan TIAN (Asian Studies, 2019)
The informed perspective presented here may rouse a sensitivity to the differences in reading Marxist philosophy from the perspective of the Inseparability of One and Many worldview and philosophy (a doctrine of internal, constitutive, relations––“intimacy”) on the part of Chinese intellectuals, particularly Mao Zedong, a great campaigner for philosophic and discursive Sinicization of Marxism. Marxism has provided an opportunity for a philosophical conversation with Chinese tradition, and this conversation was not launched by a government or official campaign, but instead by the efforts made on the part of countless grassroots intellectuals. It is argued that the reason for this was perhaps due to the fact that certain of Marx’s cosmological assumptions, in contrast to those of the main Western categories, are more capable of being understood and Sinicized in terms of particular philosophical currents in the Chinese tradition. This was particularly so for the two decades of the 1950s and 1960s, and until the end of the 1970s when Deng Xiaoping came to power and openly declared the start of his “Economic Reform” with the slogan “Socialism with Chinese Characteristics.”